From PET bottle waste to enzyme support for removal of estrogens from wastewaters - Kijenska-Gawronska, Ewa; Zdarta, Jakub; Thabit, Hani Shaker A. M.; Jesionowski, Teofil; Swieszkowski, Wojciech (ELSEVIER, 2024)
Recycling poly(ethylene terephthalate) disposables into electrospun functional membranes creates new opportunities for pollution reduction. In this study, two types of electrospun membranes made of poly(ethylene terephthalate) (PET) recycled from bottles and PET recycled from recycled bottles (rPET) were utilized in order to produce four types of biosystems with immobilized laccase for the removal of synthetic hormones micropollutants from wastewater. The enzyme was adsorbed onto the fibers directly or after a prior 24 h treatment with 10% glutaraldehyde. Obtained removal efficiency of 17 alpha-ethynylestradiol from aqueous systems was in a range of 71% to 85%, depending on the type of PET utilized for the fabrication of the membranes and the way of laccase immobilization. Moreover, fabricated biosystems showed highly improved storage stability of 72% to 85% compared to only 55% activity exhibited by free laccase after 20 days of storage. Immobilization of the laccase on the PET -based fibrous substrates also increased their thermal stability after 2 h at 50 C with preserved activity in a range of 27% to 55%, compared to only 5% registered for the free enzyme. Produced biosystems exhibited high reusability and the activity of the enzyme remains over 60% after seven catalytic cycles for all tested samples, with 79% activity after eight cycles obtained for the enzyme immobilized on PET membranes modified with glutaraldehyde prior to immobilization of laccase. The presented approach has been proven to have great potential as a sustainable tool for the enzymatic removal of synthetic hormones from wastewaters showing superior properties compared to the utilization of the enzyme in its basic form.
Keywords: PET recycling; Electrospun fibers; Enzyme immobilization; Estrogens removal; COVALENT IMMOBILIZATION; SUSTAINABLE DEVELOPMENT; LACCASE IMMOBILIZATION; POLYMERIC MATERIALS; MICROPOLLUTANTS; MEMBRANE; NEED; Biotechnology & Applied Microbiology; Engineering; Environmental Sciences & Ecology